Lohengrin opera in three acts - Wagner, Richard 1813-1883 (Arthaus Musik, 2012)
Wagner set the action of his romantic opera, Lohengrin, in the first half of the tenth century-- an instruction which director Wolfgang Weber and his stage designers Rudolf and Reinhard Heinrich took very seriously. Weber's staging underlines the dramatic sense embodied in the music, allowing the outstanding singers' full scope to express themselves in a remarkable production under Claudio Abbado. The main roles are taken by Cheryl Studer as Elsa and Placido Domingo as Lohengrin
Interpr. u.a.: Plácido Domingo [Lohengrin]. Robert Lloyd [Henry the Fowler]. Cheryl Studer [Elsa of Brabant]. Hartmut Welker [Frederick of Telramund]. Dunja Vejzovic [Ortrud]. Georg Tichy [The king's herald]. Chorus and Orchestra of the Wiener Staatsoper. Helmut Froschauer [Choreinstud.]. Claudio Abbado [Dir.]. Wolfgang Weber [Bühnenregie]. Brian Large [Filmregie]. - Live-Aufn.: Wien, Staatsoper, 1990. - Dt. gesungen. - Text des Beih.: - Untertitel: dt., engl., franz., ital., span. - Auch als Teil des DVD-Schubers "The Wagner collection" (2013, Best.-Nr. Arthaus Musik 107 527, UPC 807280752793) erschienen
Keywords: DVD-Video